PENGARUH ADMINISTRASI PENDIDIKAN DAN KINERJA GURU TERHADAP DISIPLIN BELAJAR DI SMK IT IBNU KATSIR JEMBER - Arifin, Muhammad Zainol; Neviyani, Neviyani; Andrie W, Shendy (Dharmas Education Journal (DE_Journal), 2024)
This study aims to evaluate the impact of Educational Administration and Teacher Performance on Student Discipline at SMK IT Ibnu Katsir Jember. Using a quantitative approach with an analytical survey and cross-sectional design, the research sample consists of 31 students from grades X and IX. Data analysis was performed using multiple regression and hypothesis testing. The findings indicate that Educational Administration (X1) has a negative effect on Student Discipline (Y), with a significance value of 0.916 (greater than α = 0.05) and a t-value of -0.107 (less than the t-table value of 2.048). Conversely, Teacher Performance (X2) positively and significantly affects Student Discipline, with a significance value of 0.004 (less than α = 0.05) and a t-value of 3.432 (greater than the t-table value of 2.084). Additionally, both Educational Administration and Teacher Performance together have a positive effect on Student Discipline, as indicated by a significance value of 0.003 (less than α = 0.05) and an F-value of 10.721 (greater than the F-table value of 3.33). This study highlights the critical role of Teacher Performance in enhancing Student Discipline, while Educational Administration does not show a significant impact on its own.